Do skeletal Mg/Ca ratios of Arctic rhodoliths reflect atmospheric CO2 concentrations? - Teichert, Sebastian; Voigt, Nora; Wisshak, Max (Polar Biology, 2020)
The rhodolith-forming coralline red algal species Lithothamnion glaciale is the key ecosystem engineer of rhodolith beds on the coast of Svalbard. Because it significantly increases local biodiversity in this high-Arctic environment, we investigate the potential impact of changing environmental parameters on its calcite skeleton. Using energy-dispersive X-ray spectroscopy and environmental data from the Norwegian government’s environmental monitoring, we show that the magnesium concentration within an analysed algal calcite skeleton decreases linearly and significantly over a 40-year time span (R2 = 0.267, pperm < 0.001). Mg/Ca ratios show the most significant correlation with atmospheric CO2 concentrations (R2 = 0.614, p < 0.001), and lower correlations to sea ice cover and seawater temperature. This raises the question of whether the Mg/Ca in the rhodolith skeleton is reflecting an increase in aqueous pCO2 that drives ongoing ocean acidification. Since such a change in geochemistry may alter the stability of the calcite skeleton, our results could imply an impact on the future role of the rhodoliths as ecosystem engineers and consequently on Arctic biodiversity.<br
Keywords: Coralline algae; Ecosystem engineers; Lithothamnion glaciale; Mg/Ca ratio; Ocean acidification; Rhodoliths; Svalbard